Interplay of cell-cell signalling and multicellular morphogenesis during Dictyostelium aggregation - Hofer, T; Maini, P (World Scientific, 1996)
The cellular slime mould Dictyostelium discoideum provides a paradin model system for the study of multicellular pattern formation. Its life cycle involves a route to primitive multicellular organization which has independently evolved in terrestrial species of at least four groups of microorganisms (myxobacteria, acrasiomycota-the cellular slime moulds, myxomycota, and ciliata [1]). In these species a large number of single cells (nuclei in myxomycota) form through a process of aggregation and differentiation, a fruiting body.